P234 Sputum cytokines and clinical biomarkers in severe asthma. (15th November 2016) - Shrimanker, R; Go, S; Thulborn, S; Xue, L; Pavord, ID
Abstract : Introduction: Emerging treatments for type-2 high asthma such as anti-IL-5 (mepolizumab) and anti-IL-4 and IL-13 (dupilumab) target specific cytokine pathways resulting in type-2 inflammation. Whether patients with type 2 inflammation respond equally to both treatment or have distinct IL-13 and IL-5 profiles is currently unclear. We have tested the hypothesis that these pathways may function independently of each other and that simple biomarkers can help differentiate IL-13 and IL-5 high patients. Methods: Patients with well characterised, severe asthma were evaluated with the blood eosinophil count and fractional exhaled nitric oxide (FeNO). Patients also had paired measurements of type-2 cytokines in induced sputum samples. Sputum cytokines were measured using a Luminex assay. Results: We found that there was no relationship between the blood eosinophil count and FeNO. There was a positive correlation between FeNO and sputum IL-13 (r = 0.51, p < 0.01) and blood eosinophils and sputum IL-5 (r = 0.47, p < 0.01). Conclusions: These findings suggest that readily available, non-invasive biomarkers may be able to differentiate sub-phenotypes in type-2 high asthma. Post-hoc analysis of clinical trial data of anti-IL-5 and anti-IL-4 and IL-13 treatments based on the predominant clinical biomarker would be of interest to see if these predict response to treatment. Simple biomarkers may be of use in deciding which of the emerging biological treatments to use in severe, type-2 high asthma.